Maxim of quantity and presupposition in understanding object labels. Issue 2 (4th February 2020) - Frisson, Steven; Murphy, Gregory L.
ABSTRACT: Two experiments investigated whether listeners mandatorily apply the Gricean maxim of quantity. In conversation, it is infelicitous to use a label that does not distinguish the referent ("the car" when there are two cars) or to use an unnecessarily specific label ("the convertible" when only one car is present). Subjects verified labels that picked out one of two objects, which was visually cued. Labels were at the basic or subordinate level, and the objects were related (two cars) or not (car and boat). Presuppositions were manipulated by varying determiners ("the/a car"). Responses were slower and less accurate when the basic-level name was used in the context of two related objects, suggesting that listeners prefer more distinguishable names even when the referent is unambiguous. Overly specific names did not incur a cost. Manipulating determiners had little effect. These results argue against a general use of Gricean maxims or presuppositions when identifying referents.